IL-10 plays an important role in the control of inflammation but not in the bacterial burden in S. epidermidis CNS catheter infection. Issue 1 (December 2016) - Gutierrez-Murgas, Yenis; Skar, Gwenn; Ramirez, Danielle; Beaver, Matthew; Snowden, Jessica
Abstract Background Shunt infection is a frequent and serious complication in the surgical treatment in hydrocephalus. Previous studies have shown an attenuated immune response to these biofilm-mediated infections. We proposed that IL-10 reduces the inflammatory response toStaphylococcus epidermidis (S. epidermidis ) CNS catheter infection. Methods In this study, a murine model of catheter-associatedS. epidermidis biofilm infection in the CNS was generated based on a well-established similar model forS. aureus . The catheters were pre-coated with a clinically derived biofilm-forming strain ofS. epidermidis (strain 1457) which were then stereotactically implanted into the lateral left ventricle of 8-week-old C57BL/6 and IL-10 knockout (IL-10 knockout) mice. Bacterial titers as well as cytokine and chemokine levels were measured at days 3, 5, 7, and 10 in mice implanted with sterile andS. epidermidis- coated catheters. Results Cultures demonstrated a catheter-associated and parenchymal infection that persisted through 10 days following infection. Cytokine analysis of the tissue surrounding the catheters revealed greater levels of IL-10, an anti-inflammatory cytokine, in the infected group compared to the sterile. In IL-10 KO mice, we noted no change in bacterial burdens, showing that IL-10 is not needed to control the infection in a CNS catheter infection model. However, IL-10 KO mice had increased levels of pro-inflammatory mediators in the tissues immediately adjacent to the infected catheter, as well as an increase in weight loss. Conclusions Together our results indicate that IL-10 plays a key role in regulating the inflammatory response to CNS catheter infection but not in control of bacterial burdens. Therefore, IL-10 may be a useful therapeutic target for immune modulation in CNS catheter infection but this should be used in conjunction with antibiotic therapy for bacterial eradication.